Lactate profiles of pediatric shock patients in Cipto Mangunkusumo General Hospital 2015: a pilot study - Irene Yuniar (Paediatrica Indonesiana, 2017)
Background The 2015 Surviving Sepsis Campaign (SSC) guidelines for management of shock recommend blood lactate to assess the success of resuscitation in shock. However, a study in adults found that 1/3 of septic shock patients had normal lactate levels (alactatemia) and lower mortality rates.Objective To evaluate lactate profiles, possible factors affecting lactate levels, and mortality outcomes in pediatric shock patients in the emergency room (ER) and pediatric intensive care unit (PICU).Methods This was a retrospective study on pediatric shock patients aged 1 month to 18 years in the ER or PICU from June 2014 to December 2015. Data were taken from subjects’ medical records including lactate levels, examination data required to calculate a PELOD score, and mortality outcomes.Results Of 223 shock patients evaluated, only 92 cases (41.2%) underwent lactate examinations. Of these, 59 (64.1%) had alactatemia and 33 (35.9%) had hyperlactatemia. A total of 23.7% of the alactatemia group and 36.4% of the hyperlactatemia group died, thus, the initial lactate level was not significantly associated with patient outcomes (P=0.197). The mortality rates of patients with <10% and ³10% lactate clearance were 31.3% and 17.6%, respectively (P=0.362).Conclusion In alactatemia patients, lactate level can not be used as a goal for resuscitation. Further study is needed to find a biomarker for assessing the success of pediatric shock resuscitation. Moreover, the clinical relevance of alactatemia is uncertain in pediatric shock patients.